Colorimetric Determination of Titanium as Peroxomethylenediaminetetracarboxylate - Mehra, M.C.; Easter, A. (Asian Journal of Chemistry, 2010)
The system Ti-H2O2-methylenediaminetetracarboxylate generates a ternary complex that has strong absorption at 364 nm in acetate buffered medium (pH ca. 4.5). The quantifiable concentration at lower end for Ti at 0.4 ppm is sensitive enough to warrant its analysis in low ionic contents.